Marginality and exclusion in Egypt - Bush, Ray; Ayeb, Habib (The American University in Cairo Press, 2012)
The book provides a revealing analysis of key areas of Egyptian political economy, such as labour, urbanization and the creation of slums, disability, refugees, street children, and agrarian livelihoods, reaching the impactful conclusion that marginalization does not mean total exclusion